Vanadium-based borate particles, preparation method thereof and aqueous zinc ion battery
By adopting vanadium-based borate particles with core-shell structure as the positive electrode material of aqueous zinc ion batteries, the problems of easy dissolution of vanadium-based oxides in aqueous zinc ion batteries and slow diffusion of zinc ions are solved, and the work of the battery is improved Voltage and capacity achieve efficient electrochemical performance.
Patent Information
- Application Number
- CN202411347301.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-14
AI Technical Summary
Vanadium-based oxides are used as the positive electrode material of aqueous zinc ion batteries, such as easy dissolution, slow diffusion of zinc ions, and low working voltage, which are difficult to meet practical application requirements.
Vanadium-based borate particles with core-shell structure are used as the positive electrode material, and the core includes vanadium borate (VBO3) and trivanadium borate (V3BO6). The shell is coated with conductive carbon material, and is prepared through chelation reaction and sintering processes to improve the Zinc ion diffusion speed and electron transport capacity.
The chemical and electrochemical stability of vanadium-based borate particles is achieved, and the working voltage, capacity and energy density of zinc ion batteries is improved, making it suitable for industrial production and application.
Smart Images

Figure CN119315004A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochemical energy storage, and in particular to vanadium-based borate particles and a preparation method thereof, and an aqueous zinc ion battery. Background Art
[0002] Aqueous zinc-ion battery is a new type of green and environmentally friendly energy storage device. 2+ The negative electrode uses metallic zinc, and the electrolyte uses Zn-rich 2+ Aqueous zinc-ion batteries are weakly acidic or nearly neutral zinc salts (e.g., Zn(CH3COO)2, ZnSO4, Zn(TFSI)2, Zn(CF3SO3)2, etc.). Aqueous zinc-ion batteries have the advantages of low cost, easy assembly, good safety, and high ionic conductivity. Not only are they safer than lithium-ion batteries (electrolytes are flammable and toxic), but their manufacturing costs are also lower than lithium-ion batteries. In addition, the reserves of zinc on the earth are higher than lithium, so the application prospects of aqueous zinc-ion batteries are broader. Vanadium-based oxides have the advantages of multiple valence states and high energy density, making them suitable for use as positive electrode materials for aqueous zinc-ion batteries, and have become a research hotspot in recent years. However, vanadium-based oxides used as positive electrode materials for aqueous zinc-ion batteries have problems such as easy dissolution (causing structural degradation and capacity loss), slow diffusion of zinc ions, and low operating voltage, which make it difficult to fully meet the requirements of practical applications.
[0003] Therefore, it is of great significance to develop a vanadium-based cathode material with good chemical and electrochemical stability, strong zinc ion diffusion and electron transport capabilities, and high operating voltage. Summary of the invention
[0004] The present invention aims to provide vanadium-based borate particles, a preparation method thereof and an aqueous zinc ion battery.
[0005] The technical solution adopted by the present invention is:
[0006] A vanadium-based borate particle has a core-shell structure, wherein the core comprises vanadium borate (VBO3) and trivanadium borate (V3BO6), and the shell comprises boric acid (H3BO3) and a conductive carbon material.
[0007] Preferably, the conductive carbon material is at least one of activated carbon and nitrogen-doped activated carbon.
[0008] Preferably, the particle size of the vanadium-based borate particles is 0.5 μm to 2 μm.
[0009] A method for preparing the vanadium-based borate particles as described above comprises the following steps:
[0010] 1) dispersing a vanadium source, a boric acid source and an organic chelating agent in water for chelation reaction to obtain a chelate;
[0011] 2) pre-calcining the chelate to obtain a pre-calcined product;
[0012] 3) The pre-calcined product is placed in a reducing atmosphere for sintering to obtain vanadium-based borate particles.
[0013] Preferably, a method for preparing the vanadium-based borate particles as described above comprises the following steps:
[0014] 1) dispersing a vanadium source, a boric acid source and an organic chelating agent in water for chelation reaction, and then heating and stirring until the reaction solution becomes a sol to obtain a chelate;
[0015] 2) drying the chelate and grinding it into powder, pre-calcining it, and then cooling it and grinding it to obtain a pre-calcined product;
[0016] 3) placing the pre-calcined product in a reducing atmosphere for sintering and cooling to obtain vanadium-based borate particles.
[0017] Preferably, the vanadium source in step 1) is ammonium metavanadate (NH4VO3), vanadyl sulfate (VOSO4), vanadyl oxalate (VOC2O4), vanadyl acetylacetonate (C 10 H 14 O5V), vanadium acetylacetonate (C 15 H 21 At least one of vanadium pentoxide (V2O5), vanadium dioxide (VO2), vanadium trioxide (V2O3), and vanadium tetrachloride (VCl4).
[0018] Preferably, the boric acid source in step 1) is at least one of boron trioxide (B2O3), boric acid (H3BO3), ammonium borate (NH4HB4O7·3H2O), ammonium pentaborate (NH4B5O8), and boron powder.
[0019] Preferably, the organic chelating agent in step 1) is polyvinyl alcohol ([C2H4O] n ), citric acid (C6H8O7), oxalic acid (H2C2O4), ascorbic acid (VC), and ethylenediamine (C2H8N2).
[0020] Preferably, the molar ratio of vanadium in the vanadium source to boron in the boric acid source in step 1) is 1:1.0-1.5.
[0021] Preferably, the molar ratio of the vanadium source to the organic chelating agent in step 1) is 1:1-3.
[0022] Preferably, the chelating reaction in step 1) is carried out at a temperature of 60°C to 100°C.
[0023] Preferably, the drying in step 2) is carried out at a temperature of 60°C to 180°C.
[0024] Preferably, the drying in step 2) is carried out in an air atmosphere.
[0025] Preferably, the pre-firing in step 2) is carried out in an air atmosphere, a reducing atmosphere or a protective atmosphere.
[0026] Preferably, the reducing atmosphere is one of a CO-H2 mixed atmosphere, a N2-H2 mixed atmosphere, a H2-Ar mixed atmosphere, an ammonia atmosphere, a hydrogen atmosphere, a biocarbon atmosphere, and a carbon-nitrogen mixed atmosphere.
[0027] Preferably, the protective atmosphere is one of N2 atmosphere, Ar atmosphere, He atmosphere and Ne atmosphere.
[0028] Preferably, the pre-firing in step 2) is carried out at a temperature of 200° C. to 500° C., and the pre-firing time is 3 h to 6 h.
[0029] Preferably, the reducing atmosphere in step 3) is one of a CO-H2 mixed atmosphere, a N2-H2 mixed atmosphere, a H2-Ar mixed atmosphere, an ammonia atmosphere, a hydrogen atmosphere, a biocarbon atmosphere, and a carbon-nitrogen mixed atmosphere.
[0030] Preferably, the sintering in step 3) is carried out at a temperature of 600° C. to 1000° C., and the sintering time is 8 h to 20 h.
[0031] A positive electrode material comprises the vanadium-based borate particles.
[0032] An aqueous zinc ion battery comprises the above-mentioned positive electrode material.
[0033] The beneficial effects of the present invention are as follows: the vanadium-based borate particles of the present invention have a faster zinc ion diffusion rate and a stronger electron transport capacity, good chemical and electrochemical stability, good compatibility with aqueous electrolytes, and a simple preparation method, a short preparation time, and a low production cost. An aqueous zinc ion battery made using the vanadium-based borate particles as a positive electrode material has a high operating voltage, a large capacity, a high energy density, and excellent rate performance and cycle performance, and is suitable for large-scale industrial production and application.
[0034] Specifically:
[0035] 1) The vanadium-based borate particles of the present invention contain vanadium borate (VBO3), which as a borate has a very high specific capacity, and the "inductive effect" of borate can increase the output voltage of the vanadium-based borate particles and reduce the dissolution of active substances in the aqueous electrolyte, which is beneficial to improve the output voltage and cycle stability of the aqueous zinc ion battery;
[0036] 2) The vanadium-based borate particles of the present invention contain trivanadium borate (V3BO6), which has high electrical conductivity and electrochemical activity. Compounding it with vanadium borate and further coating the surface with a conductive carbon material can effectively solve the problem of low electrical conductivity of vanadium borate, thereby improving the overall electrical conductivity of the vanadium-based borate particles;
[0037] 3) The vanadium-based borate particles of the present invention contain boric acid (H3BO3), which can improve the compatibility between the vanadium-based borate particles and the aqueous electrolyte and further inhibit the dissolution of the active material;
[0038] 4) The aqueous zinc ion battery made of the vanadium-based borate particles of the present invention as the positive electrode material has a high specific capacity and a high operating voltage (when the operating voltage window is 0.2V to 1.8V, the maximum discharge capacity can reach 374mAh / g, and the output voltage is 0.1V to 0.2V higher than that of the aqueous zinc ion battery made of ordinary vanadium oxide as the positive electrode material);
[0039] 5) The present invention organically combines liquid phase chelation and solid phase reaction to prepare vanadium-based borate particles. Compared with the traditional high-temperature solid phase method, the raw material reaction is more thorough and the reaction temperature is lower. High-purity vanadium-based borate particles can be synthesized, which reduces the manufacturing cost of vanadium-based borate particles and improves the safety of the synthesis process. In addition, the carbonization of the organic chelating agent during the sintering process can form a conductive network between the vanadium-based borate particles, thereby effectively improving the overall conductivity and electrochemical activity of the vanadium-based borate particles.
[0040] 6) The boric acid source used in the preparation of vanadium-based borate particles in the present invention is abundant in resources, which can effectively reduce the raw material cost of industrial production of vanadium-based borate particles, thereby effectively reducing the overall manufacturing cost of aqueous zinc ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is the XRD pattern of the vanadium-based borate particles in Example 1.
[0042] Figure 2 This is the SEM image of the vanadium-based borate particles in Example 1.
[0043] Figure 3 This is the charge and discharge curve of the aqueous zinc ion battery assembled with the vanadium-based borate particles in Example 1.
[0044] Figure 4 This is the XRD pattern of the vanadium-based borate particles in Example 2.
[0045] Figure 5 This is the charge and discharge curve of the aqueous zinc ion battery assembled with the vanadium-based borate particles in Example 2.
[0046] Figure 6 This is the XRD pattern of the vanadium-based borate particles in Example 3.
[0047] Figure 7 This is the charge and discharge curve of the aqueous zinc ion battery assembled with the vanadium-based borate particles in Example 3. DETAILED DESCRIPTION
[0048] The present invention will be further explained and illustrated below in conjunction with specific embodiments.
[0049] Embodiment 1:
[0050] A vanadium-based borate particle, the preparation method of which is as follows:
[0051] 1) dissolving NH4VO3 and NH4B5O8 in deionized water at a molar ratio of V to B of 1:1.4, then adding C6H8O7·H2O in an amount equal to that of NH4VO3, and stirring at a constant temperature of 80°C until the reaction solution becomes a sol, thereby obtaining a chelate;
[0052] 2) baking the chelate in an oven at 60° C. for 18 h, grinding it into powder, and then pre-calcining it at 400° C. for 4 h in an air atmosphere, cooling it naturally, and then grinding it to obtain a pre-calcined product;
[0053] 3) The pre-calcined product was ground and placed in a H2-Ar mixed atmosphere (the volume fraction of H2 was 5%), sintered at 700°C for 20 hours, and naturally cooled to obtain vanadium-based borate particles (referred to as sample 1).
[0054] Performance Test:
[0055] 1) The X-ray diffraction (XRD) pattern of the vanadium-based borate particles in this embodiment is as follows: Figure 1 shown.
[0056] Depend on Figure 1 It can be seen that in this embodiment, vanadium-based borate particles whose main phases are vanadium borate (VBO3) and trivanadium borate (V3BO6) are obtained.
[0057] 2) The scanning electron microscope (SEM) image of the vanadium-based borate particles in this example is as follows: Figure 2 (a and b represent different magnifications).
[0058] Depend on Figure 2 It can be seen that the vanadium-based borate particles are irregularly shaped particles with a particle size of 0.5 μm to 2 μm.
[0059] 3) The vanadium-based borate particles in this example were used as the positive electrode material to assemble a button-type aqueous zinc ion battery (the negative electrode was a metal zinc sheet, and the electrolyte was a ZnSO4 aqueous solution with a concentration of 2 mol / L), and then the electrochemical performance was tested by constant current charge and discharge method (current density was 100 mA / g, voltage window was 0.2 V to 1.8 V), and the charge and discharge curves obtained were as follows: Figure 3 shown.
[0060] Depend on Figure 3 It can be seen that the discharge specific capacity of the aqueous zinc ion battery reaches 279mAh / g.
[0061] Embodiment 2:
[0062] A vanadium-based borate particle, the preparation method of which is as follows:
[0063] 1) dissolving NH4VO3 and NH4B5O8 in deionized water at a molar ratio of V to B of 1:1.5, then adding C6H8O7·H2O in an amount equal to that of NH4VO3, and stirring at a constant temperature of 80°C until the reaction solution becomes a sol, thereby obtaining a chelate;
[0064] 2) baking the chelate in an oven at 80° C. for 12 h, grinding it into powder, and then pre-calcining it at 400° C. for 4 h in an air atmosphere, cooling it naturally, and then grinding it to obtain a pre-calcined product;
[0065] 3) The pre-calcined product was ground and placed in a H2-Ar mixed atmosphere (H2 volume fraction is 5%), sintered at 800°C for 20 hours, and naturally cooled to obtain vanadium-based borate particles (referred to as sample 2; irregularly shaped core-shell structured particles, the particle size of which is very close to the vanadium-based borate particles in Example 1).
[0066] Performance Test:
[0067] 1) The XRD pattern of the vanadium-based borate particles in this embodiment is as follows Figure 4 shown.
[0068] Depend on Figure 4 It can be seen that in this embodiment, vanadium-based borate particles whose main phases are vanadium borate (VBO3) and trivanadium borate (V3BO6) are obtained.
[0069] 2) The vanadium-based borate particles in this example were used as the positive electrode material to assemble a button-type aqueous zinc ion battery (the negative electrode was a metal zinc sheet, and the electrolyte was a ZnSO4 aqueous solution with a concentration of 2 mol / L), and then the electrochemical performance was tested by constant current charge and discharge method (current density was 100 mA / g, voltage window was 0.2 V to 1.8 V), and the charge and discharge curves obtained were as follows: Figure 5 shown.
[0070] Depend on Figure 5It can be seen that the discharge specific capacity of the aqueous zinc ion battery reaches 295mAh / g.
[0071] Embodiment 3:
[0072] A vanadium-based borate particle, the preparation method of which is as follows:
[0073] 1) dissolving NH4VO3 and NH4B5O8 in deionized water at a molar ratio of V to B of 1:1.5, then adding C6H8O7·H2O in an amount equal to that of NH4VO3, and stirring at a constant temperature of 80°C until the reaction solution becomes a sol, thereby obtaining a chelate;
[0074] 2) baking the chelate in an oven at 60° C. for 10 h, grinding it into powder, and then pre-calcining it at 400° C. for 4 h in an air atmosphere, cooling it naturally, and then grinding it to obtain a pre-calcined product;
[0075] 3) The pre-calcined product was ground and placed in a H2-Ar mixed atmosphere (H2 volume fraction is 5%), sintered at 900°C for 20 hours, and naturally cooled to obtain vanadium-based borate particles (referred to as sample 3; irregularly shaped core-shell structured particles, the particle size of which is very close to the vanadium-based borate particles in Example 1).
[0076] Performance Test:
[0077] 1) The XRD pattern of the vanadium-based borate particles in this embodiment is as follows Figure 6 shown.
[0078] Depend on Figure 6 It can be seen that in this embodiment, vanadium-based borate particles whose main phases are vanadium borate (VBO3) and trivanadium borate (V3BO6) are obtained.
[0079] 2) The vanadium-based borate particles in this example were used as the positive electrode material to assemble a button-type aqueous zinc ion battery (the negative electrode was a metal zinc sheet, and the electrolyte was a ZnSO4 aqueous solution with a concentration of 2 mol / L), and then the electrochemical performance was tested by constant current charge and discharge method (current density was 100 mA / g, voltage window was 0.2 V to 1.8 V), and the charge and discharge curves obtained were as follows: Figure 7 shown.
[0080] Depend on Figure 7 It can be seen that the discharge specific capacity of the aqueous zinc ion battery reaches 374mAh / g.
[0081] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A vanadium-based borate particle, characterized in that: The invention has a core-shell structure, wherein the inner core comprises vanadium borate and trivanadium borate, and the outer shell comprises boric acid and a conductive carbon material.
2. The vanadium-based borate particles according to claim 1, characterized in that: The conductive carbon material is at least one of activated carbon and nitrogen-doped activated carbon.
3. The vanadium-based borate particles according to claim 1 or 2, characterized in that: The particle size of the vanadium-based borate particles is 0.5 μm to 2 μm.
4. A method for preparing vanadium-based borate particles according to any one of claims 1 to 3, characterized in that: The following steps are involved: 1) dispersing a vanadium source, a boric acid source and an organic chelating agent in water for chelation reaction to obtain a chelate; 2) pre-calcining the chelate to obtain a pre-calcined product; 3) The pre-calcined product is placed in a reducing atmosphere for sintering to obtain vanadium-based borate particles.
5. The preparation method according to claim 4, characterized in that: The vanadium source in step 1) is at least one of ammonium metavanadate, vanadyl sulfate, vanadyl oxalate, vanadyl acetylacetonate, vanadium acetylacetonate, vanadium pentoxide, vanadium dioxide, vanadium trioxide, and vanadium tetrachloride; the boric acid source in step 1) is at least one of boron trioxide, boric acid, ammonium borate, ammonium pentaborate, and boron powder; the organic chelating agent in step 1) is at least one of polyvinyl alcohol, citric acid, oxalic acid, ascorbic acid, and ethylenediamine.
6. The preparation method according to claim 4 or 5, characterized in that: The molar ratio of vanadium in the vanadium source in step 1) to boron in the boric acid source is 1:1.0-1.5; the molar ratio of vanadium source in step 1) to organic chelating agent is 1:1-3.
7. The preparation method according to claim 4 or 5, characterized in that: Step 2) The pre-firing is carried out in an air atmosphere, a reducing atmosphere or a protective atmosphere; Step 3) The reducing atmosphere is one of a CO-H2 mixed atmosphere, a N2-H2 mixed atmosphere, a H2-Ar mixed atmosphere, an ammonia atmosphere, a hydrogen atmosphere, a biochar atmosphere, and a carbon-nitrogen mixed atmosphere.
8. The preparation method according to claim 4 or 5, characterized in that: The chelating reaction in step 1) is carried out at a temperature of 60°C to 100°C; the pre-firing in step 2) is carried out at a temperature of 200°C to 500°C, and the pre-firing time is 3h to 6h; the sintering in step 3) is carried out at a temperature of 600°C to 1000°C, and the sintering time is 8h to 20h.
9. A positive electrode material, characterized in that: The vanadium-based borate particles according to any one of claims 1 to 3 are included.
10. An aqueous zinc ion battery, characterized in that: Contains the positive electrode material according to claim 9.